PEMANTAUAN DAN PENGENDALIAN KERUSAKAN LAHAN UNTUK PRODUKSI BIOMASSA DI KAWASAN KABUPATEN KUNINGAN JAWA BARAT - Andrianto Kusumoarto; Ryan Hidayat (Lakar: Jurnal Arsitektur, 2018)
Abstract: The purpose of this activity is provided the information is stored the damaged the ground for the production of biomass in district brass .In addition , provide information penanggulangannya efforts and models the prevention of damages land through sig and maxent. Determine the point of observation ( ploting ), of course associated with an elevation / topography, ( good land conditions, while, and critical ) in each subdistrict of village.Hence, the number of a plot every berbeda-beda the number of plotnya village, besides depends on if the existing problems didesa masing-masing the, also deals with the management pattern of the community surrounding land.